TINJAUAN YURIDIS TENTANG BATAS UISA NIKAH BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Novriawanda Novriawanda; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Constitution Number one of 1974 concerning marriage has undergone revisions or changes related to the rules for the age limit for marriage contained in Article 7 paragraph (1), these rules are considered no longer relevant to conditions in society. Therefore, the government set a new rule regarding the age limit for marriage with the enactment of Constitution Number 16 of 2019 concerning Amendments to Constitution Number 1 of 1974 about Marriage. The focus of this research were the factors that influence of Constitution Number 16 of 2019 and the legal impact caused by changes the Constitution.This research is a normative juridical research that conceptualizes law as a norm including values, positive law and court decisions. Legal materials were collected by means of document studies and library research, namely by combining primary, secondary and tertiary legal materials related to the age limit for marriage based on Constitution Number 16 of 2019. The analysis of legal materials was carried out by descriptive analysis, namely explaining or explain what it is about a legal event or legal condition based on primary legal norms.Based on the results of the research there were several influences from the enactment of Constitution Number 16 of 2019 including: Philosophically, the change in the age limit for marriage in Constitution Number 16 of 2019 is a commitment of the state in realizing the life of the nation and state that is far from treatment discriminatory. Sociologically, it is the government's effort to prevent early marriage, but this determination is not accompanied by changes to the rules regarding marriage dispensation. So, the number of applications for marriage dispensation in the Religious Courts increase. Juridically, the change in the age limit for marriage is a revision of the previous regulation which is considered irrelevant with the current state of society. So, the current marriage age limit based on Constitution Number 16 of 2019 is that marriage is only permitted if a man and a woman have reached the age of 19 (nineteen) years. The legal impacts arising from the amendment of Constitution Number one of 1974 to Constitution Number 16 of 2019 concerning changes to the marriage age limit arise from various aspects, including sociological aspects, philosophical aspects, juridical aspects, health aspects and psychological aspects.Key words: Age Limit, Constitution Number 16 of 2019